Randomized Controlled Trial of Early Versus Delayed Statin Therapy in Patients With Acute Ischemic Stroke: ASSORT Trial (Administration of Statin on Acute Ischemic Stroke Patient). Issue 11 (November 2017) - Yoshimura, Shinichi; Uchida, Kazutaka; Daimon, Takashi; Takashima, Ryuzo; Kimura, Kazuhiro; Morimoto, Takeshi; Tanada, Shuichi; Iida, Tomoko; Kuroda, Junko; Nose, Akinori; Tatebayashi, Kotaro; Shimizu, Fuminori; et al.
Abstract : Background and Purpose—: Several studies suggested that statins during hospitalization were associated with better disability outcomes in patients with acute ischemic stroke, but only 1 small randomized trial is available. Methods—: We conducted a multicenter, open-label, randomized controlled trial in patients with acute ischemic strokes in 11 hospitals in Japan. Patients with acute ischemic stroke and dyslipidemia randomly received statins within 24 hours after admission in the early group or on the seventh day in the delayed group, in a 1:1 ratio. Statins were administered for 12 weeks. The primary outcome was patient disability assessed by modified Rankin Scale at 90 days. Results—: A total of 257 patients were randomized and analyzed (early 131, delayed 126). At 90 days, modified Rankin Scale score distribution did not differ between groups ( P =0.68), and the adjusted common odds ratio of the early statin group was 0.84 (95% confidence interval, 0.53–1.3; P =0.46) compared with the delayed statin group. There were 3 deaths at 90 days (2 in the early group, 1 in the delayed group) because of malignancy. Ischemic stroke recurred in 9 patients (6.9%) in the early group and 5 patients (4.0%) in the delayed group. The safety profile was similar between groups. Conclusions—: Our randomized trial involving patients with acute ischemic stroke and dyslipidemia did not show any superiority of early statin therapy within 24 hours of admission compared with delayed statin therapy 7 days after admission to alleviate the degree of disability at 90 days after onset. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT02549846. Abstract : Supplemental Digital Content is available in the text.